Heart failure therapy in patients with advanced cancer receiving specialized palliative care (EMPATICC trial) - Anker, Markus; Mahabadi, Amir A; Totzeck, Matthias; Tewes, Mitra; Khan, Muhammad Shahzeb; Mincu, Raluca I; Hendgen-Cotta, Ulrike B; Michel, Lars; Mathew, Baicy; Drescher, Ophelia; Schuler, Martin; Keller, Ulrich; et al. (European heart journal, 2025)
Advanced cancer may resemble a heart failure (HF)-like phenotype marked by cardiac wasting, dyspnoea, congestion, and/or physical dysfunction. The trial evaluated safety and efficacy of HF therapy among patients with advanced cancer receiving specialized palliative care to improve patients’ self-care ability.Patients with stage 4 solid tumours with a life expectancy of 1-6 months receiving specialized palliative care were enrolled. Patients were required to meet at least two cardiovascular risk criteria and at least one criterion for functional limitation. Participants were randomized 1:1 to receive optimized HF therapy (up to four drugs: sacubitril/valsartan, empagliflozin, ivabradine, ferric carboxymaltose) or placebo in a double-blind setting. The primary hierarchical endpoint included: (i) days alive and able to wash oneself, (ii) ability to walk 4 m, and (iii) self-reported patient global assessment (PGA) of subjective well-being, during the 30-day placebo-controlled phase.In five centres, 93 patients were randomized. The primary endpoint did not differ between groups (win ratio 0.95, 95% confidence interval [CI] 0.57-1.58; P = .83). Overall, mortality was 32% at 30 days (not different between groups). In patients alive at 30 days, HF therapy reduced N-terminal pro-B-type natriuretic peptide levels by 41% (P = .040), increased left ventricular ejection fraction by 2.9% (P = .036), and improved PGA scores (odds ratio 0.22, 95% CI 0.06-0.75; P = .016).In a population with advanced cancer receiving specialized palliative care and high early mortality, optimized HF therapy did not improve patients’ self-care ability. Among survivors at 30 days, improvements in quality of life measures and cardiac biomarkers suggest potential benefit of individualized HF therapy, which is hypothesis generating and needs validation.
Gesehen am 20.01.2026